Study to identify the novel neuromodulatory site of eurycoma longifolia jack (tongkat ali) in rat central nervous system (CNS) / Norhasimah Ali @ Yaakob - Ali @ Yaakob, Norhasimah (2017)
Eurycoma longifolia Jack is the herbal medicinal plant of South-East Asian origin, locally known as Tongkat Ali. Traditionally, it is used for its antimalarial, aphrodisiac, anti-diabetic, antimicrobial, anti-pyretic, anti-stress and anti-aging activities which have been proved scientifically. In Malaysia and South East Asia, demand for the therapeutic products application containing Tongkat Ali to treat male sexual dysfunction is increasing year by year. However, the neuro-anatomical functional site is still not known. The objective of this study is to localize the functional neuroanatomical site (s) of Eurycoma longifolia Jack extract in rat central nervous system (CNS) using immunohistochemistry technique. Control group of male Spraguedawley rats (six, weight 180-200 g) was received intraperitoneal injection (i.p.) of normal saline and experimental rats received i.p injection of Tongkat Ali (8mg/kg) of body weight. The expression of c-Fos protein immunoreactivity was detected in freeze frozen serial sections (40 μm) in dorsal and ventral horn of cervical spinal cord. C-Fos immunostaining was identified as black spot. Statistical analysis was performed using student t-test. P<0.001 was set as significant. Present study demonstrated that compare to control significant increased in number of c-Fos expression was detected in the sensory and motor nucleus of the spinal cord. To our knowledge, this is the first report in localization the functional sites of Tongkat Ali in rat motor and sensory nucleus. Result indicates that Tongkat Ali may have neuromodulatory function in motor and sensory nucleus. Further study is essential to investigate the therapeutic effect of Tongkat Ali in motor (e.g., temporomandibular) and sensory system (e.g., pain) disorders.